Affinity of mismatch-binding protein MutS for heteroduplexes containing different mismatches. - Brown, J; Brown, T; Fox, K (2001)
We have used bandshift analysis to measure the interaction between the Escherichia coli mismatch-binding protein MutS and synthetic DNA fragments containing all possible DNA mismatches as well as an unpaired T (DeltaT). The order of affinity is found to be DeltaT>GT>GG>AA approximately TT approximately TC>CA>GA>CC>GC. We find that the affinity for GT mismatches is affected by the flanking sequence and decreases in the order G(n)C(n)>(GC)(n)>A(n)T(n)>(AT)(n). Studies with base analogues show good binding to phiT (where phi represents 1',2'-dideoxyribose), but much weaker binding to Gphi.